Effect of interfacial transition zone on creep behavior of steel fiber-reinforced concrete. (3rd October 2022) - Xu, Zehua; Zhao, Qingxin; Guo, Weichao; Zhang, Jinrui; Yu, Junchao; Wang, Dongli; Bai, Yanying
Highlights: A SFRC creep prediction model considering ITZ was established. The role of ITZ in SFRC was revealed. The effects of relevant factors on SFRC creep were analyzed. The key factors affecting SFRC creep were determined. Abstract: To explore the interface transition zone (ITZ) effect on the creep behavior of steel fiber-reinforced concrete (SFRC), this study proposed a three-phase creep prediction model based on the mesomechanical shear lag theory. The model verification was performed using available creep data, and three influencing factors were analyzed. The proposed creep prediction model well described the creep behavior of SFRC, revealing the ITZ's role in it. The specific creep values of SFRC at the loading age of 365d with 1, 2, and 3% steel fiber contents exceeded those assessed without the ITZ effect account by 9.8, 6.3, and 54.0%, respectively. The effects of the ITZ elastic modulus and thickness, as well as the steel fiber length-to-diameter ratio on the SFRC creep, were analyzed via the proposed model. The grey relational analysis theory can characterize the correlation between related factors and various variations, so as to determine the key factors. Through this theory, it was revealed that the ITZ elastic modulus variation had the most significant effect on the SFRC creep.